LOCAL COMMUNITY VIEWS ON THE SUPPORT OF RURAL TOURISM: BENEFIT PERSPECTIVES OF ECONOMY, SOCIAL, ENVIRONMENT AND BUREAUCRACYS - Hasan Basri; Muhammad Ali; Amrullah; Muhamad Juaini (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
This research aims to examine how the perception of tourism benefits influences the support for tourism development in Loyok Village, moderated by political bureaucracy. Conducted through a quantitative methodology, the research gathered data from 183 Loyok Village residents via online surveys distributed through Google Forms using SmartPLS SEM. The research reveals a lack of significant correlation between the perceived benefits of tourism and the community's support for its development in Loyok Village. The anticipated economic and social benefits did not substantially influence community support. Furthermore, a possible explanation for these findings is that the majority of respondents are not directly involved in the tourism industry. Most participants are engaged in agriculture or other sectors, limiting their direct experience of tourism's tangible benefits. The research suggests that those who directly benefit from tourism tend to have positive attitudes towards its development, while those who do not exhibit negative perceptions